Tolerance And Peace As Enhacing Factor In Sharia Economic Growth - Alifah; Hamidah; Anisa; Rizal (LP2M IAIN Palopo, 2024)
This study investigates the relationship between tolerance, peace, and sharia economic growth through a literature review approach. The focus is on understanding how tolerance and peace play roles as an enhancing factor in Sharia economic growth. High tolerance and maintained peace are considered crucial in creating a conducive environment for the development of a Sharia-based economy. Through a literature review, it was found that tolerance opens up opportunities for financial inclusion and investment in the Sharia economy, while peace provides the stability necessary for sustainable economic growth. The results of this study are expected to provide deeper insights into the importance of tolerance and peace in strengthening the Sharia economy, as well as provide a foundation for further research in this field.